A Futuristic Silicon-Carbide (SiC) Based Electric- Vehicle Fast Charging/Discharging (FC/dC) Station - JAYDEEP SAHA (Institute of Electrical and Electronics Engineers [Society Publisher], 2023)
10.1109/JESTPE.2022.3223417